Generalized livedo reticularis: A rare variety - Pallavi Goyal; Surabhi Dayal; Priyadarshini Sahu (Wolters Kluwer Medknow Publications, 2019)
Livedo reticularis can present with progressive ischemia and diffuse cutaneous involvement with or without any evidence of systemic diseases. Livedo reticularis (LR) is a livedoid discoloration of the skin in a reticular pattern. We report the case of a 30-year-old male who presented with an asymptomatic, red-colored, net-like rash all over the body for 4 years. Laboratory investigations were performed to rule out any systemic involvement. Biopsy showed perivascular mononuclear cell infiltrate and occasional arteriole showed thickening of the wall with obliteration of the lumen and extensive collagenization in dermis, suggesting a diagnosis of LR. The patient was advised oral pentoxifylline 400 mg thrice daily with oral nifedipine 10 mg twice daily, and mild improvement was seen after 6 weeks of therapy.